Effects of climate change on food security and nutrition in India: A systematic review - Das, Abhishek; Kumar, Shalander; Kasala, Kavitha; Nedumaran, S.; Paithankar, Pradnya; Kumar, Abhay; Jain, Ayushi; Avinandan, Vijay (Elsevier, 2025)
Climate change poses a complex challenge to food and nutritional security, impacting human health, well-being, and sustainable development. India, facing heightened vulnerability in agriculture and a growing population surpassing 1.3 billion, requires a detailed examination of these effects. This examination will serve as a crucial resource for shaping policies, directing research efforts, and fostering public discourse. This systematic review thoroughly analyzes the impact of climate change on food and nutritional security in India. Examining 231 articles, the study delves into various dimensions, including availability, accessibility, utilization, and stability. The review utilized Web of Science, PubMed, and CABI review, employing 100 different keywords. Temperature variations, erratic rainfall, and extreme weather events disrupt crops, livestock, poultry, and aquaculture production (food availability), leading to food shortages, income loss, and elevated food prices (accessibility), especially affecting low-income groups. Indirectly, climate change affects livelihoods and incomes, exacerbating inequalities and leading to the displacement of marginalized communities (stability), thereby escalating food insecurity and malnutrition (utilization). However, few studies cover diverse aspects such as the influence of climate change on traditional crops, nutritional value, agricultural biodiversity, food distribution systems, indigenous food systems, and nutrition outcomes, particularly for vulnerable groups like women and children. Hence, there is a pressing need for a more holistic and integrated approach to tackle the impacts of climate change on food and nutrition security in India.